2019
DOI: 10.1002/ppap.201900093
|View full text |Cite
|
Sign up to set email alerts
|

On the role of secondary electron emission in capacitively coupled radio‐frequency plasma sheath: A theoretical ground

Abstract: We propose a theoretical ground for emissive capacitively coupled radio-frequency (rf) plasma sheath under low pressure. The rf sheath is assumed to be collisionless and oscillates with external source. A known sinusoidal voltage instead of current is taken as prerequisite to derive sheath dynamics. Kinetic studies are performed to determine mean wall potential as a function of secondary emission coefficient and applied voltage amplitude, with which the complete mean direct current sheath is resolved. Analytic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The mean RF sheath determines the ion incident energy at solid surface, and is therefore crucial in view of the numerous applications related to CCP [1] . Mean RF sheath potential is a function of applied voltage amplitude and the emission coefficient, but simultaneously considering the two factors leaves no analytical solution to the RF sheath [10] . To qualitatively illustrate the influence of trap state on sheath properties, here ad hoc analyses are given using the example of floating boundary, the general trend for RF sheath in CCP should be analogous.…”
Section: ⅲ Theoretical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean RF sheath determines the ion incident energy at solid surface, and is therefore crucial in view of the numerous applications related to CCP [1] . Mean RF sheath potential is a function of applied voltage amplitude and the emission coefficient, but simultaneously considering the two factors leaves no analytical solution to the RF sheath [10] . To qualitatively illustrate the influence of trap state on sheath properties, here ad hoc analyses are given using the example of floating boundary, the general trend for RF sheath in CCP should be analogous.…”
Section: ⅲ Theoretical Analysesmentioning
confidence: 99%
“…In previous works, it has been confirmed by experiments that Secondary Electron Emission (SEE) can significantly modify important plasma parameters, such as particle/power balance, temperature and density [5,6] . Theoretical studies indicated that SEE significantly modified the important discharge parameters [8,9] , theoretical analyses express RF sheath as function of source amplitude and SEE coefficient, giving quantitive current-voltage characteristic, sheath capacitance, conductance in the presence of boundary electron emission [10,11] . Apart from experiment and theory, numerical simulation also provides insight into physical details of PSI in CCP.…”
mentioning
confidence: 99%
“…Adopted simulation parameters are listed below to help replicate simulation results: source frequency 13.56 MHz, bulk plasma density 0 = 5 × 10 14 The simulation produces noise-free data for better understanding of sheath physics, similar methods were used in several previous works related to plasma sheath [28][29][30][31] . More detailed algorithm was shown in our previous works of bounded plasma 15,32 .…”
mentioning
confidence: 99%
“…Conduction current prevails displacement current in bulk plasma and field in bulk plasma is weak. But in this letter we will show that the bias can be primarily consumed by bulk plasma and electric field in plasma center needs not to be shielded by sheathes, due to intense boundary emission.Numerous studies have been done regarding boundary emission in CCP, but its influences are mostly assumed to be unessential 4,[8][9][10][11][12][13][14][15] . The steady flux of ion 𝛤 𝑖 produces a surface emission flux 𝛤 𝑒𝑚 = 𝛾 𝑖 𝛤 𝑖 due to ion-induced secondary electron emission (SEE), with 𝛾 𝑖 the emission coefficient.…”
mentioning
confidence: 99%
See 1 more Smart Citation